Pengaruh Digital Banking, Literasi Keuangan, dan Promosi E-Commerce terhadap Perubahan Pola Menabung Mahasiswa - Susilowati, Nenden; Rafi, Muhammad; Fitrianingrum, Dewi; Nabila, Novi Rahma; Febriansyah, Rizaldi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
This study aims to analyze the partial influence of digital banking, financial literacy, and e-commerce promotions on changes in the savings patterns of 2023 Management students at the Faculty of Economics and Business, Yogyakarta State University. The problem focuses on  digital banking usage, financial literacy levels, and the presence of e-commerce promotions as indicators of influence on changes in the savings patterns experienced by Management students. This study uses a quantitative approach through an associative method, with a sample of 185 respondents. The sampling method for this study uses non-probability sampling through purposive sampling techniques. Data were collected through questionnaires and analyzed using validity, reliability, classical assumptions, and partial tests. The results of the study show that X1 (digital banking) has a positive and significant effect on Y (saving patterns), X2 (financial literacy) has no significant effect on saving patterns (Y), and X3 (e-commerce promotions) has no significant effect on student saving patterns (Y). Concludes that student saving patterns are influenced by the use of digital banking, but e-commerce promotions and financial literacy levels do not have a significant effect on student saving patterns.